Bio-inspired energy scavenging in wireless ad hoc network - Ponnusamy, V. (Institute of Electrical and Electronics Engineers Inc., 2017)
Wireless ad hoc network differs from traditional network in terms of energy constraint of battery-backed devices. In most of the situation, wireless nodes operate on powered batteries without human intervention and have limited computation and energy capabilities. Very limited work has been conducted on energy harvesting approach for sustainanble energy management for networks where human intervention is undesirable. Moreover existing work on matured solar energy harvesting is not desirable for indoor shadowy networks and other potential energy sources are not mature for existing work. This study will propose animal behavior based environmental energy harvesting for wireless ad hoc networks. The proposed sustainable energy property yields better lifetime and self-healing capabilities in wireless ad hoc networks. This focuses on animal behavior algorithms to overcome the issues of poor energy management in wireless ad hoc networks. With this, bird foraging behavior on central place foraging (CPF) analogous to energy harvesting from the environment using central place foraging approach is proposed with detailed mapping. The given bio-inspired mechanism provides a self-healing mechanism for sustainable energy management yielding longer lifetime in ad hoc wireless networks. © 2017 IEEE.